2017
DOI: 10.3126/ajms.v8i3.16847
|View full text |Cite
|
Sign up to set email alerts
|

Tubercular mastitis: An institutional experience from a tertiary care centre of northern India

Abstract: Background: Tuberculous mastitis (TM) is a rare extra pulmonary presentation of tuberculosis. It may be problematic to distinguish from carcinoma breast, a condition with which it may coexist.  Fine needle aspiration cytology (FNAC) / biopsy are indispensable for diagnosis and tuberculosis culture when positive may be very valuable to guide antimicrobial therapy.Aims and Objectives:  To disseminate the message to the concerned expertise that it can present a diagnostic problem on radiological and microbiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Breast may become infected by tuberculosis infection by direct spread of ductal infection, haematogenous spread, lymphatic spread or spread from pleura or chest wall. (2,5,9). Secondary BTB is caused by retrograde lymphatic spread as suggested by Cooper, which is presumed by presence of ipsilateral axillary lymphadenitis in 33-50% cases of BTB as in our study it was 37% cases.…”
Section: International Journal Of Medical and Biomedical Studies (Ijmsupporting
confidence: 59%
See 3 more Smart Citations
“…Breast may become infected by tuberculosis infection by direct spread of ductal infection, haematogenous spread, lymphatic spread or spread from pleura or chest wall. (2,5,9). Secondary BTB is caused by retrograde lymphatic spread as suggested by Cooper, which is presumed by presence of ipsilateral axillary lymphadenitis in 33-50% cases of BTB as in our study it was 37% cases.…”
Section: International Journal Of Medical and Biomedical Studies (Ijmsupporting
confidence: 59%
“…Mckeown and Wilkinson classified BTB based on pathogenesis as primary when the breast lesion was the only foci of tuberculosis and secondary when there was other foci elsewhere in the body apart from breast. (5,9) As per Vassilakos primary BTB is rare but many studies and in our study primary BTB was found in 89% of cases. This is debatable as breast tissue is resistant to tuberculous infection and EPTB foci in lymph node may be easily missed clinico-radiologically.…”
Section: International Journal Of Medical and Biomedical Studies (Ijmsupporting
confidence: 54%
See 2 more Smart Citations